Persistence and effectiveness of nonbiologic systemic therapies for moderate‐to‐severe psoriasis in adults: a systematic review - Mason, K.J. (John Wiley and Sons Inc., 2019)

(untitled) (Br J Dermatol)
BACKGROUND: The persistence and effectiveness of systemic therapies for moderate‐to‐severe psoriasis in current clinical practice are poorly characterized. OBJECTIVES: To systematically review observational studies investigating the persistence and effectiveness of acitretin, ciclosporin, fumaric acid esters (FAE) and methotrexate, involving at least 100 adult patients with moderate‐to‐severe psoriasis, exposed to therapy for ≥ 3 months. METHODS: MEDLINE, Embase, the Cochrane Library and PubMed were searched from 1 January 2007 to 1 November 2017 for observational studies reporting on persistence (therapy duration or the proportion of patients discontinuing therapy during follow‐up) or effectiveness [improvements in Psoriasis Area and Severity Index (PASI) or Physician's Global Assessment (PGA)]. This review was registered with PROSPERO, number CRD42018099771. RESULTS: Of 411 identified studies, eight involving 4624 patients with psoriasis were included. Variations in the definitions and analyses of persistence and effectiveness outcomes prevented a meta‐analysis from being conducted. One prospective multicentre study reported drug survival probabilities of 23% (ciclosporin), 42% (acitretin) and 50% (methotrexate) at 1 year. Effectiveness outcomes were not reported for either acitretin or ciclosporin. The persistence and effectiveness of FAE and methotrexate were better characterized, but mean discontinuation times ranged from 28 to 50 months for FAE and 7·7 to 22·3 months for methotrexate. At 12 months of follow‐up, three studies reported that 76% (FAE), 53% (methotrexate) and 59% (methotrexate) of patients achieved ≥ 75% reduction in PASI, and one reported that 76% of FAE‐exposed patients achieved a markedly improved or clear PGA. CONCLUSIONS: The comparative persistence and effectiveness of acitretin, ciclosporin, FAE and methotrexate in real‐world clinical practice in the past decade cannot be well described due to the inconsistency of the methods used.